Clinical Outcome of Viral Respiratory Tract Infections in Hospitalized Adults in Norway: High Degree of Inflammation and Need of Emergency Care for Cases With Respiratory Syncytial Virus - Debes, Sara; Haug, Jon Birger; de Blasio, Birgitte Freiesleben; Lindstrøm, Jonas Christoffer; Jonassen, Christine Monceyron; Dudman, Susanne Gjeruldsen (Frontiers in Medicine, 2022)
Background: The clinical features and outcomes of viral respiratory tract infections (RTIs) in adults have not been thoroughly studied, especially the respiratory syncytial virus (RSV) disease burden. It has become apparent that outbreaks of RSV in the elderly are associated with increased hospitalization rates. However, little data exists on the severity of such viral RTIs in adults, particularly the need for hospitalization, respiratory support and intensive care. Methods: We conducted a retrospective observational single-center study at Østfold Hospital Trust, Norway, during three winter seasons 2015 – 2018. Patients ≥18 years with either influenza A, influenza B, RSV A/B, human metapneumovirus, parainfluenza virus 1-4 or adenovirus detected in respiratory specimens were included, if they were hospitalized 14 days prior or following the detection date, with signs of RTI. Hospital records on treatment and outcome were investigated, as well as mortality of all causes up to 30 days from discharge. Results: Of the 1222 infection events that were included, influenza A was the most frequent virus detected (39%), while 179 infection events (14.6%) were due to RSV. Influenza B counted for 24% of the infection events, human metapneumovirus 13%, parainfluenza virus 9% and adenovirus 1%. Patients admitted with RSV more often suffered from COPD and congestive heart failure than patients with influenza A. In addition, RSV patients were overrepresented in the urgent response NEWS score (National Early Warning Score) category ≥5. Most RSV patients also showed signs of more severe inflammation, with WBC≥11.1 x109/L and CRP >100 mg/L, and they were more often treated with antibiotic agents during their hospital stay. However, we found no differences in the need for ICU admission or mortality. Conclusion: Patients with RSV had more often high values for markers of inflammation and elevated NEWS score when compared to patients hospitalized with other common respiratory viruses. Taken into account that they suffered more frequently from comorbidities like COPD, these patients needed hospitalization more urgently.These findings highlight the need for further investigations on RSV disease in adults and the elderly.